2013
DOI: 10.1038/jid.2012.457
|View full text |Cite
|
Sign up to set email alerts
|

Topically Applied Flightless I Neutralizing Antibodies Improve Healing of Blistered Skin in a Murine Model of Epidermolysis Bullosa Acquisita

Abstract: Epidermolysis bullosa (EB) is a chronic inheritable disease that leads to severe blistering and fibrosis. Previous studies have shown that the actin cytoskeletal protein flightless I (Flii) impairs wound healing associated with EB. Using a mouse model of EB acquisita (EBA), the effect of "mopping up" Flii using Flii-neutralizing antibodies (FnAbs) before, during, and after blister formation was determined. FnAbs, incorporated into a cream vehicle and applied topically to the skin, penetrated into the basal epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 33 publications
5
56
0
Order By: Relevance
“…In accordance to observations in would healing, overexpression of Flii led to a more severe clinical phenotype in antibody transfer-induced EBA (408), while pharmacological inhibition had therapeutic effects in mice with EBA (409). These findings indicate that processes controlling would healing are important to resolve inflammation and blistering, opening new avenues in our understanding of EBA pathogenesis, as well as pointing to so far neglected potential therapeutic targets.…”
Section: Autoantibody-induced Inflammationsupporting
confidence: 82%
“…In accordance to observations in would healing, overexpression of Flii led to a more severe clinical phenotype in antibody transfer-induced EBA (408), while pharmacological inhibition had therapeutic effects in mice with EBA (409). These findings indicate that processes controlling would healing are important to resolve inflammation and blistering, opening new avenues in our understanding of EBA pathogenesis, as well as pointing to so far neglected potential therapeutic targets.…”
Section: Autoantibody-induced Inflammationsupporting
confidence: 82%
“…This reduced Flii expression in Flii+/− mice significantly impaired blister formation in experimental EBA [133]. Subsequent studies demonstrated that topical treatment with Flii-neutralizing antibodies has therapeutic effects in this model of EBA [134]. These observations point towards significant contribution of pathways that are involved in resolving cutaneous involvement.…”
Section: Mechanisms Of Autoantibody-induced Tissue Injurymentioning
confidence: 99%
“…Beneficial effects following the topical application once daily for 9 days of pooled polyclonal IgG in atopic dermatitis (eczema) patients were reported in a previous small scale clinical trial involving six patients, with an antiinflammatory effect which was comparable to that obtained using topical corticosteroids (Burek-Kozlowska et al, 1994). Penetration into intact skin may also become possible when antibodies are encapsulated into liposomes (Balsari et al, 1994), incorporated into aqueous cetomacrogol cream (Kopecki et al, 2013) or formulated in a hydrogel cream as with low-MW ($25 kDa) scFv antibodies (Hansen, 2013). A phase IIa clinical trial initiated by the Swiss company Delenex Therapeutics AG is currently underway (NCT01936337) to investigate the topical administration of anti-TNF alpha scFv antibodies to target mild to moderate psoriasis (Hansen, 2013).…”
Section: Dermal Usementioning
confidence: 94%
“…The antibody was applied to the ulcers either as a 10 mg/mL solution covered with an adhesive sheet or as a gel formulation (0.45, 1 or 4.5 mg/g) under a hydrofiber dressing adhesive sheet. Although a cocktail containing additional healing agents (Attia et al, 2014;Burek-Kozlowska et al, 1994;Jackson et al, 2012;Kopecki et al, 2013;Pinho et al, 2014;Ruzehaji et al, 2014) may have an improved effect, this initial pioneering study is important in demonstrating the feasibility of the topical route in the clinical setting and again suggests that a high local concentration of anti-TNF favors prompt and definitive healing. Supporting evidence was recently provided by Teich & Klugmann (Teich & Klugmann, 2014), who reported a rapid improvement in refractory pyoderma gangrenosum, a reaction causing local skin ulceration, following the topical application of Infliximab in a sterile hydroxylethyl cellulose gel.…”
Section: Dermal Usementioning
confidence: 99%